ON FORMAL TOOLS IN THE SOFTWARE ENGINEERING - Arslan Enikeev; Mahfoodh Bilal Ahmed Mohammed; Elina Stepanova (European Scientific Journal, ESJ, 2015)
This paper presents an overview of different approaches to a creation of the technique of software application development based on the integrated development environment which contains a model and tools for its implementation. Our results in this field are also presented. We study a formal model specification and analysis tools which may have potential for the software application development.